Different understandings, different responses: experiences of racism among highly educated, second generation Black Germans - Piwoni, Eunike (Frontiers in Sociology, 2025)
This article argues that there is a close relationship between individuals’ understandings of specific incidents of racism, their ideas of how racism operates, and their (repertoires of) responses to such incidents. The argument is based on a qualitative interview study with 21 highly educated Black Germans with at least one parent born outside Germany, and draws on both the extant literature on responses to experiences of ethnoracial exclusion and research into how people make sense of such experiences. The analysis specifically explores two contrasting types of interviewees: Type 1 felt that they were constantly and potentially always affected by racism and had a broad knowledge of racism. These interviewees recounted many different incidents, many of which they clearly labelled as “racist.” Type 1 interviewees reported a variety of response options, with direct confrontation being one of them. In stark contrast, Type 2 respondents tended to normalise the relatively few incidents they mentioned or indicate only feelings of unease. They also believed that they were largely unaffected by racism, had a less deep understanding of racism and tended to respond to incidents of exclusion in ways that allowed the encounter to continue without disruption. Overall, the study calls for greater attention to racialised people’s meaning-making in relation to concrete incidents of exclusion and to their knowledge of racism. This requires methodological adaptations to qualitative interview research, which remains the most popular method for exploring experiences of racism. In particular, the study highlights the importance of understanding the ways in which respondents talk about their experiences (categorisation, indication of feelings of unease, and normalisation). It also emphasises the need to go beyond considering only interviewees’ responses to direct questions about their experiences of racism and/or discrimination and/or incidents clearly categorised by interviewees as, for example, “racist.” Moreover, reconstructing interviewees’ knowledge about racism offers a path towards understanding not only their sense-making but also their repertoires of responses. This, in turn, provides insight into why individuals of comparable class position and educational background respond to racism in different ways.